Analisa Waktu Pelaksanaan Preservasi Jalan Namlea - Marloso - Mako - Modanmohe – Namrole - Sari, Novita; Jamlaay, Octovianus; Titaley, Henriette Dorothy (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Unwanted challenges are frequently encountered during the execution of building projects, one of which is the occurrence of delays brought on by a variety of circumstances, such as minor equipment damage and personnel shortages. To overcome this, alternative options are needed that can be used to complete the project such as adding working hours (overtime). The case study in this study is the Namlea - Marloso - Mako - Modanmohe - Namrole Road Preservation project. This study analyzes the implementation time using the CPM (critical path method) method and the crashing method. The data needed in this study include the S curve, a recapitulation of project cost calculations, a list of Budget Plans (RAB), analysis of work unit prices and a list of wages for workers and heavy equipment. The purpose of this study is to obtain the duration of the implementation time using the CPM method, identify critical paths and then carry out crashing to obtain the duration of the acceleration time with the alternative of adding 3 hours of overtime. From the results of the analysis carried out using the CPM method, the implementation time was obtained for 359 days (51 weeks) and consisted of 1 critical path with 12 activities. The crashing method is only focused on labor-intensive activities with an alternative of adding 3 hours of overtime. After acceleration with the crashing method, a duration of 345 days (49 weeks) was obtained, a reduction of 14 days from the normal duration of 359 days (51 weeks).